Prolonged length of stay after posterior surgery for cervical spondylotic myelopathy in patients over 65 years of age. (September 2016) - De la Garza-Ramos, Rafael; Goodwin, C. Rory; Abu-Bonsrah, Nancy; Jain, Amit; Miller, Emily K.; Neuman, Brian J.; Protopsaltis, Themistocles S.; Passias, Peter G.; Sciubba, Daniel M.
Highlights: A large inpatient database was used to identify elderly patients who underwent posterior surgery for cervical myelopathy. Prolonged length of stay (PLOS) was defined as stay beyond 6 days in this study. Predictive factors for PLOS included alcohol abuse, deep vein thrombosis, myocardial infarction, pneumonia, and others. PLOS was associated with significantly higher mortality rates and total hospital charges compared to the control group. Abstract: Prolonged length of stay (PLOS) has been associated with increased hospital resource utilization and worsened patient outcomes in multiple studies. In this study, we defined and identified factors associated with PLOS after posterior surgery for cervical spondylotic myelopathy in patients over the age of 65. PLOS was defined as length of stay beyond the "prolongation point" (that is, the day after which discharge rates begin to decline). Using the United States Nationwide Inpatient Sample database, 2742 patients met inclusion criteria, out of whom 16.5% experienced PLOS (stay beyond 6 days). After multivariate analysis, increasing age was independently associated with PLOS (odds ratio [OR] 1.04, 95% confidence interval [CI] 1.02–1.06). Multiple comorbid conditions were associated with PLOS, including alcohol abuse (OR 3.85, 95% CI 1.87–7.94), congestive heart failure (OR 1.72, 95% CI 1.11–2.64), obesity (OR 1.70, 95% CI 1.14–2.55), and deficiency anemia (OR 1.44, 95% CI 1.01–2.05); the strongest associated operative parameter was blood transfusion (OR 2.39, 95% CI 1.75–3.28). Major complications independently associated with PLOS were deep vein thrombosis (OR 18.32, 95% CI 6.50–51.61), myocardial infarction (OR 8.98, 95% CI 2.92–27.56), pneumonia (OR 6.67, 95% CI 3.17–14.05), acute respiratory failure (OR 6.27, 95% CI 3.43–11.45), hemorrhage/hematoma (OR 5.04, 95% CI 2.69–9.44), and implant-related complications (OR 2.49, 95% CI 1.24–4.98). Average total hospital charges for patients who experienced PLOS were 122, 965 US dollars, compared to 76, 870 for the control group (p < 0.001). Mortality for patients who experienced PLOS was 2.7% versus 0.5% for patients who did not epxerience PLOS (p < 0.001). In conclusion, patients over the age of 65 who underwent posterior surgery for cervical myelopathy and stayed over 6 days in hospital were defined as having PLOS. Hospital charges and mortality rates were significantly higher for patients who experienced PLOS. Potentially modifiable and/or preventable risk factors were also identified.